1991
DOI: 10.1109/10.133205
|View full text |Cite
|
Sign up to set email alerts
|

Neural network and conventional classifiers for fluorescence-guided laser angioplasty

Abstract: In laser angioplasty, fluorescence spectra of targeted tissue may be used to classify the tissue as atherosclerotic or normal and guide selective laser ablation of atherosclerotic plaque. Here, the ability of the back-propagation and K-nearest neighbors techniques to classify arterial fluorescence spectra is investigated. Both methods are competitive with other classification schemes. The relative performance of variations on both techniques is used to make inferences about the geometry of the classification t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
1
10
0
5
Order By: Relevance
“…These morphocompositional differences have been reported to be reflected on the spectral emission trends of the 2 types of arterial tissue. 13,24 Higher values of the emission intensity were reported 18,37 for normal aortic wall (intensity in the red range: Ϸ80% of main peak value) relative to those found for normal coronary artery (Ϸ65%) in this study. Also, the time-dependent emission of normal aorta was shorter (Ϸ11 ns at the main peak region) than that of normal coronary artery (Ϸ14 ns).…”
Section: Comparison Between Aortic and Coronary Artery Wall Fluorescencementioning
confidence: 61%
See 4 more Smart Citations
“…These morphocompositional differences have been reported to be reflected on the spectral emission trends of the 2 types of arterial tissue. 13,24 Higher values of the emission intensity were reported 18,37 for normal aortic wall (intensity in the red range: Ϸ80% of main peak value) relative to those found for normal coronary artery (Ϸ65%) in this study. Also, the time-dependent emission of normal aorta was shorter (Ϸ11 ns at the main peak region) than that of normal coronary artery (Ϸ14 ns).…”
Section: Comparison Between Aortic and Coronary Artery Wall Fluorescencementioning
confidence: 61%
“…The spectral emission of coronary artery has been reported for both ex vivo 9,10,23,24 and in vivo 12,13 investigation and for various excitation wavelengths: 308 nm, 12 325 nm, 23,24 337 nm, 10 and 476 nm. 9 The time-integrated spectra of normal coronary artery described by our study are in agreement with the emission spectra reported by the research groups that used 337 nm and 325 nm for excitation.…”
Section: Spectral and Temporal Fluorescence Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations